Supporting Young Children's Physical Development through Tailored Motor Competency Interventions within a School Setting - Ellie Huggett; Kristy Howells (MDPI AG, 2024)
Background/Objectives: This study investigated how tailored motor competency (MC) interventions within a bespoke Scheme of Work (SOW) can support young children's physical development (PD) by enhancing fine motor skills (FMS) and gross motor skills (GMS). The objective was to enable children to meet curriculum developmental physical milestones. Methods: The longitudinal case study design was conducted over 19 weeks across three academic terms and focused on 25 children (12 boys and 13 girls aged between 5 and 6 years old). Interventions within the SOW were evaluated at six points to assess effectiveness and to make adjustments. Data collection included observations on FMS and GMS development. Results: Statistically significant improvements were observed in FMS and GMS after implementing the MC interventions. Notable improvements included hopping, running, climbing, kicking, catching, and using scissors (p < 0.05). Conclusions: The study underscores the importance of holistic approaches to PD, highlighting the need for early intervention and the crucial role of educators. The findings advocate for strategically planned MC interventions and practitioner observations to achieve longitudinal improvements in PD. The study recommends nationwide implementation to enhance PD outcomes, preparing children for lifelong and life-wide MC.